Indole-2-Carboxamide Derivative LG25 Inhibits Triple-Negative Breast Cancer Growth By Suppressing Akt/mTOR/NF-κB Signalling Pathway - Xu X; Rajamanickam V; Shu S; Liu Z; Yan T; He J; Liu Z; Guo G; Liang G; Wang Y (Dove Medical Press, 2019)
Xiaohong Xu,1 Vinothkumar Rajamanickam,1 Sheng Shu,1 Zhoudi Liu,1 Tao Yan,1 Jinxin He,1 Zhiguo Liu,1 Guilong Guo,2 Guang Liang,1 Yi Wang1 1Chemical Biology Research Center, School of Pharmaceutical Sciences, Wenzhou Medical University, Wenzhou, Zhejiang 325035, People’s Republic of China; 2Department of Surgical Oncology, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou, Zhejiang 325000, People’s Republic of ChinaCorrespondence: Yi WangChemical Biology Research Center, School of Pharmaceutical Sciences, Wenzhou Medical University, Wenzhou, Zhejiang 325035, People’s Republic of ChinaTel/Fax +8657785773060Email yi.wang1122@wmu.edu.cnBackground: Triple-negative breast cancer (TNBC) is an aggressive subtype of breast cancer which is associated with poor patient outcome and lack of targeted therapy. Our laboratory has synthesized a series of indole-2-carboxamide derivatives. Among this series, compound LG25 showed a favorable pharmacological profile against sepsis and inflammatory diseases. In the present study, we investigated the chemotherapeutic potential of LG25 against TNBC utilizing in vitro and in vivo models.Methods: Changes in cell viability, cell cycle phases and apoptosis were analyzed using MTT, clonogenic assay, FACS and Western blotting assays. The anti-cancer effects of LG25 were further determined in a xenograft mouse model.Results: Our findings reveal that LG25 reduced TNBC viability in a dose-dependent manner. Flow cytometric and Western blot analyses showed that LG25 enhances G2/M cell cycle arrest and induced cell apoptosis. In addition, LG25 treatment significantly inhibited Akt/mTOR phosphorylation and nuclear translocation of nuclear factor-κB (NF-κB). These inhibitory activities of LG25 were confirmed in mice implanted MDA-MB-231 TNBC cells.Conclusion: Our studies provide experimental evidence that indole-2-carboxamide derivative LG25 effectively targeted TNBC in preclinical models by inducing cell cycle arrest and apoptosis, through suppressing Akt/mTOR/NF-κB signaling pathway.Keywords: indole analog, triple-negative breast cancer, cell cycle arrest, apoptosis, Akt, mTOR